Anode electrode sheet, method of manufacturing the same, battery using the same, and electronic device

CN115088101BActive Publication Date: 2026-10-23NINGDE AMPEREX TECHNOLOGY LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202080096492.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-03-11
Publication Date
2026-10-23
Estimated Expiration
2040-03-11

AI Technical Summary

Technical Problem

[0004]但是,由于碳材料本身对锂的结合能较大,约为-1eV,现有的碳骨架阳极极片在锂金属沉积过程中沉积位置不可控,导致锂金属沉积不均匀,进一步地,由于锂金属沉积不均匀,阳极极片在循环过程中体积变化大,使得这种基于现有碳骨架阳极极片制造的锂离子电池的能也有待提高

Benefits of technology

[0025]本申请提供一种阳极极片,阳极极片包括集流体和活性层,其中活性层中包括:多孔碳骨架、硅纳米颗粒以及锂金属,硅纳米颗粒和锂金属位于多孔碳骨架的中,在循环过程中,由于纳米硅能够自发地与来自阴极的锂金属发生合金化反应,因此可以提供锂沉积所需的位点,从而有效地调控锂的沉积位置,使循环过程中锂优先沉积在孔隙中,使锂金属沉积更加均匀,从而减少阳极极片在循环过程中的体积变化,抑制锂枝晶的生长。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115088101B_ABST
    Figure CN115088101B_ABST
Patent Text Reader

Abstract

An anode electrode sheet, a preparation method thereof, a battery using the electrode sheet, and an electronic device, wherein the anode electrode sheet comprises a current collector (1) and an active layer (2), and the active layer (2) comprises a porous carbon skeleton (3) and silicon nanoparticles (4) and lithium metal (5) in the porous carbon skeleton (3). The battery using the electrode sheet can reduce the volume change of the anode electrode sheet during the cycle process, inhibit the growth of lithium dendrites, improve the safety of the lithium ion battery, and enable the battery using the anode electrode sheet to have a higher energy density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of batteries, specifically to an anode electrode and its preparation method, as well as batteries and electronic devices using the electrode. Background Technology

[0002] Lithium-ion batteries are characterized by high energy density, high operating voltage, low self-discharge rate, small size, and light weight, making them widely used in consumer electronics. With the rapid development of electric vehicles and mobile electronic devices, the performance requirements for lithium-ion batteries are also increasing, such as higher energy density, safety, and cycle performance.

[0003] To improve the performance of lithium-ion batteries, such as Figure 1 As shown, existing technologies employ anode framework technology, which uses carbon materials to construct a porous carbon framework on the anode electrode. During battery discharge, lithium metal is stripped from the anode and embedded into the cathode material, while the carbon framework maintains its shape, thus the volume of the anode electrode does not decrease. During battery charging, lithium metal is stripped from the cathode and deposited onto the anode electrode. Lithium can be stored in the pores of the carbon framework, thereby maintaining the stability of the anode electrode volume. Furthermore, the carbon framework can disperse the current, reduce the local current density, thereby improving the deposition morphology, reducing lithium dendrites, increasing lithium deposition density, and ultimately improving the performance of lithium-ion batteries.

[0004] However, due to the relatively high binding energy of carbon materials to lithium (approximately -1 eV), the deposition position of existing carbon-framed anodes is uncontrollable during lithium metal deposition, resulting in uneven lithium metal deposition. Furthermore, due to the uneven lithium metal deposition, the anode undergoes significant volume changes during cycling, which means that the energy of lithium-ion batteries manufactured based on existing carbon-framed anodes needs to be improved. Summary of the Invention

[0005] The purpose of this application is to provide an anode electrode and its preparation method, as well as a battery and electronic device using the electrode, to improve the uniformity of lithium metal deposition. The specific technical solution is as follows:

[0006] A first aspect of this application provides an anode electrode comprising a current collector and an active layer, the active layer comprising a porous carbon framework and silicon nanoparticles and lithium metal located within the porous carbon framework.

[0007] In one embodiment of this application, the sum of the volumes of the porous carbon framework and the silicon nanoparticles accounts for 10% to 60% of the total volume of the active layer.

[0008] In one embodiment of this application, the total volume ratio of the porous carbon framework to the silicon nanoparticles is 5:1 to 100:1.

[0009] In one embodiment of this application, the lithium metal content in the active layer is 0.001 to 3 mg / cm³. 2 .

[0010] In one embodiment of this application, the thickness of the active layer is 1 to 100 μm.

[0011] In one embodiment of this application, the strength of the porous carbon skeleton is not less than 200 GPa.

[0012] In one embodiment of this application, the porosity of the porous carbon framework is 40% to 90%.

[0013] In one embodiment of this application, the material of the current collector includes at least one of the following: copper, nickel, titanium, molybdenum, iron, zinc, stainless steel and their alloys, or carbon and graphene.

[0014] The second aspect of this application provides a method for preparing an anode sheet as described in the first aspect above, comprising:

[0015] Porous carbon framework sheets are placed in a CVD device, and a silane-containing gas is introduced to deposit nano-silicon particles to obtain the deposited porous carbon framework sheets.

[0016] Under a protective gas atmosphere, molten lithium metal is brought into contact with the deposited porous carbon skeleton sheet, so that the lithium metal fills the pores of the deposited porous carbon skeleton sheet to obtain an active layer.

[0017] The active layer is placed on the current collector, and hot pressing is used to combine the active layer and the current collector to obtain the anode electrode.

[0018] In one embodiment of this application, the deposition time of the nano-silicon particles is controlled to be 5 to 120 min.

[0019] A third aspect of this application provides a lithium-ion battery, comprising: a cathode electrode;

[0020] Anode plate;

[0021] A separating membrane, the separating membrane being located between the cathode electrode and the anode electrode; and

[0022] Electrolyte;

[0023] The anode electrode is the anode electrode described in the first aspect above.

[0024] A third aspect of this application provides an electronic device comprising a lithium-ion battery as described in the third aspect above.

[0025] This application provides an anode electrode, which includes a current collector and an active layer. The active layer includes a porous carbon framework, silicon nanoparticles, and lithium metal. The silicon nanoparticles and lithium metal are located in the porous carbon framework. During cycling, the nano-silicon can spontaneously alloy with the lithium metal from the cathode, thus providing the sites required for lithium deposition. This effectively controls the lithium deposition location, allowing lithium to preferentially deposit in the pores during cycling, resulting in more uniform lithium metal deposition. This reduces the volume change of the anode electrode during cycling and inhibits the growth of lithium dendrites. Attached Figure Description

[0026] To more clearly illustrate the technical solutions of the embodiments of this application and the prior art, the drawings used in the embodiments and the prior art are briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other technical solutions can be obtained based on these drawings without creative effort.

[0027] Figure 1 This is a schematic diagram of the structure of an existing anode framework;

[0028] Figure 2 This is a schematic diagram of the anode electrode structure according to one embodiment of this application;

[0029] Figure 3 This is a schematic diagram of the anode electrode structure according to another embodiment of this application;

[0030] Figure 4 This is a schematic diagram of the anode sheet in another embodiment of this application. Detailed Implementation

[0031] To make the objectives, technical solutions, and advantages of this application clearer, the following detailed description is provided with reference to the accompanying drawings and embodiments. Obviously, the described embodiments are merely some, not all, of the embodiments of this application. Based on the embodiments of this application, all other technical solutions obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0032] Existing lithium-ion battery anode materials, such as graphite, allow lithium ions to be embedded within the graphite layer structure during charging. This graphite layer acts as a framework, providing storage space for lithium. However, lithium-ion batteries with pure lithium metal electrodes lack this framework structure. Consequently, the anode electrode undergoes drastic volume changes during charging and discharging, typically varying in thickness from 8 to 200 μm, leading to decreased cycle performance. Furthermore, during charging, lithium deposits on the current collector surface of the anode electrode. Due to uneven current density and lithium-ion concentration in the electrolyte, some deposition sites experience excessively rapid deposition. These lithium deposits grow from the lithium metal matrix in a synaptic-like manner, continuing to grow and even branching, eventually forming sharp lithium dendrites. The presence of lithium dendrites significantly reduces the deposition density, resulting in a decrease in the battery's energy density. For example, in some lithium-ion batteries, the actual lithium metal deposition density is only 0.2 g / cm³. 3 It is approximately [value missing], much smaller than the true density of lithium metal, which is 0.534 g / cm³. 3 Due to the loose deposition of lithium metal, the battery's energy density will decrease by more than 100 Wh / L. Furthermore, lithium dendrites may puncture the separator, causing a short circuit and leading to battery failure, thus affecting battery safety.

[0033] In view of this, this application provides an anode electrode, see [link to relevant documentation]. Figure 2 and Figure 3 ,in, Figure 2 This is a top view of the anode plate of one embodiment of this application. Figure 3 This is a cross-sectional view of an anode electrode according to one embodiment of this application, including: a current collector 1 and an active layer 2, wherein the active layer 2 includes a porous carbon framework 3 and silicon nanoparticles 4 and lithium metal 5 located in the porous carbon framework 3. It is understood that the silicon nanoparticles 4 and lithium metal 5 can be discretely distributed in the porous carbon framework 3 or continuously distributed in the porous carbon framework 3. This application does not exclude the possibility that a small portion of the silicon nanoparticles 4 and lithium metal 5 are located on the surface of the porous carbon framework.

[0034] In one embodiment of this application, the active layer 2 may be composed of a porous carbon framework 3, silicon nanoparticles 4, and lithium metal 5. The porous carbon framework 3 may be a membrane-like structure with numerous pores, which may be micropores or other shapes. Furthermore, the porous carbon framework 3 possesses sufficient strength, for example, not less than 200 GPa, to maintain a stable morphology and internal space. During charging, the porous carbon framework 3 provides a stable space for lithium metal deposition within its numerous pores; during discharging, as the lithium content at the anode decreases, the porous carbon framework 3 maintains a stable structure and internal space, preventing drastic anode shrinkage. On the other hand, the porous carbon framework 3, being a carbon-based material, possesses excellent ionic and electronic conductivity, thus providing conductive channels. Furthermore, the porous carbon framework 3 has a high specific surface area, effectively dispersing the current during charging and discharging, reducing current density, and forming a more uniform electric field, thereby improving the uniformity of lithium deposition and suppressing lithium dendrite growth.

[0035] However, the inventors discovered that the porous carbon framework 3 can only maximize its function if the lithium metal deposition location is effectively controlled. If the lithium metal is deposited on the surface of the anode electrode, the anode electrode will still undergo drastic volume changes during cycling, thus making it difficult for the porous carbon framework 3 to perform its intended function.

[0036] Therefore, the active layer of this application also includes silicon nanoparticles 4, which are located in the porous carbon framework 3. The silicon nanoparticles 4 can spontaneously undergo an alloying reaction with lithium metal, with an alloying potential of about 0.2V. Therefore, they can provide the sites required for lithium metal deposition, thereby effectively controlling the deposition location of lithium metal and causing lithium metal to preferentially deposit in the pores of the porous carbon framework 3 during cycling, rather than on the surface of the anode electrode.

[0037] The active layer of this application may also include pre-added lithium metal 5. It is understood that lithium metal 5 is the anode active material. Because lithium metal has a higher specific capacity than materials such as carbon and silicon (lithium metal has a specific capacity of 3860 mAh / g, silicon has a specific capacity of 3600 mAh / g, while carbon's specific capacity is only 372 mAh / g), the battery using this anode will also have a higher energy density. Of course, the aforementioned lithium metal 5 can be pre-added during the preparation of the anode, or it can be entirely transferred from the cathode, or it can be obtained by combining pre-added lithium and cathode-transferred lithium.

[0038] In one embodiment of this application, silicon nanoparticles 4 can be attached to a porous carbon framework 3, and lithium metal 5 can be filled into the porous carbon framework 3.

[0039] In one embodiment of this application, the sum of the volumes of the porous carbon framework and silicon nanoparticles accounts for 10% to 60% of the total volume of the active layer. The anode electrode prepared by the above ratio of porous carbon framework to silicon nanoparticles has a lower volume expansion rate and a higher cycle count after being made into a lithium-ion battery.

[0040] In one embodiment of this application, the total volume ratio of the porous carbon framework to silicon nanoparticles can be from 5:1 to 100:1. That is, in the active layer 2, the ratio between the total volume of the porous carbon framework and the total volume of silicon nanoparticles is from 5:1 to 100:1. When there are fewer silicon nanoparticles in the active layer, their guiding effect on lithium metal deposition is insufficient. Therefore, some lithium metal is deposited on the surface of the anode electrode, resulting in a large volume expansion of the anode electrode. When the amount of silicon nanoparticles in the active layer is moderate, lithium metal is deposited inside the anode electrode, and the volume expansion of the anode electrode is smaller. However, when there are too many silicon nanoparticles in the active layer, since the silicon nanoparticles themselves do not participate in the reaction during cycling, too many silicon nanoparticles can actually affect the deposition of lithium metal. By controlling the volume of silicon nanoparticles in the active layer within the above-mentioned range in terms of volume ratio, the anode electrode can have a lower volume expansion rate and a higher cycle count after being manufactured into a lithium-ion battery.

[0041] In one embodiment of this application, the lithium metal content in the active layer is 0.001 to 3 mg / cm³. 2 If the pre-replenished lithium content is too low, it will not improve the battery's cycle performance; if the pre-replenished lithium content is too high, it may reduce safety.

[0042] In one embodiment of this application, the thickness of the active layer is 1 to 100 μm.

[0043] In one embodiment of this application, the porosity of the porous carbon framework is 40% to 90%.

[0044] The material of the current collector in this application is not particularly limited and can be any material well known to those skilled in the art. For example, the material of the current collector may include, but is not limited to, at least one of copper, nickel, titanium, molybdenum, iron, zinc, stainless steel and their alloys, or conductive inorganic materials such as carbon or graphene. These materials may be used alone or in combination of two or more.

[0045] The anode electrode provided in this application can provide sites for lithium deposition during cycling because nano-silicon can spontaneously alloy with lithium metal from the cathode. This effectively controls the deposition location of lithium, allowing lithium to be preferentially deposited in the pores during cycling, resulting in more uniform lithium metal deposition. This reduces the volume change of the anode electrode during cycling and inhibits the growth of lithium dendrites.

[0046] This application also provides a method for preparing an anode sheet, comprising the following steps:

[0047] Composite of porous carbon framework with silicon nanoparticles:

[0048] A porous carbon framework sheet is placed in a CVD (CVD) device, and a silane-containing gas is introduced to deposit nano-silicon particles, resulting in the deposited porous carbon framework sheet. The porous carbon framework sheet can be pre-prepared by carbonization with a glucose solution, and the silane gas can be methylene silane or ethyl silane, etc.

[0049] Pre-replenishment of lithium:

[0050] In a protective gas atmosphere, molten lithium metal is brought into contact with deposited porous carbon framework sheets, causing the lithium metal to fill the pores of the deposited porous carbon framework sheets, thus forming an active layer. The protective gas atmosphere can be argon gas with a water content below 1 ppm and an oxygen content below 1 ppm. When molten lithium metal comes into contact with the deposited porous carbon framework sheets, lithium spontaneously fills the pores of the sheets.

[0051] Preparation of the anode sheet:

[0052] The active layer is placed on the current collector, and hot-pressed to bond the active layer and the current collector together, thus producing the anode electrode. After the anode electrode is produced, it can be punched into a size of 40*60mm for use in assembling stacked cells.

[0053] In this application, by depositing silicon nanoparticles on a porous carbon framework sheet, the lithium metal deposition of the anode electrode is made more uniform during cycling, reducing the volume change of the anode electrode during cycling. Furthermore, by pre-replenishing lithium metal, the battery using the anode electrode of this application has higher cycle performance.

[0054] One embodiment of this application also provides a lithium-ion battery, including: a cathode electrode, an anode electrode, a separator, and an electrolyte, wherein the separator is located between the cathode electrode and the anode electrode, and the anode electrode is the anode electrode described in any of the above embodiments.

[0055] In the lithium-ion battery of this application, since the nano-silicon in the anode electrode can spontaneously undergo an alloying reaction with lithium metal from the cathode, it can provide the sites required for lithium deposition, thereby effectively controlling the lithium deposition position, so that lithium is preferentially deposited in the pores during cycling, making the lithium metal deposition more uniform, thereby reducing the volume change of the anode electrode during cycling, suppressing the growth of lithium dendrites, and improving the safety of the lithium-ion battery.

[0056] One embodiment of this application also provides an electronic device including the lithium-ion battery described in the above embodiment. In this electronic device, the lithium-ion battery used has a more uniform lithium metal deposition, thereby reducing the volume change of the anode electrode during cycling, suppressing the growth of lithium dendrites, and making the electronic device safer.

[0057] There are no particular limitations on the cathode electrode used in this application; any cathode electrode known in the art may be used. For example, cathode electrodes containing lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, or lithium nickel cobalt manganese oxide or lithium nickel cobalt aluminum oxide may be used.

[0058] There are no particular limitations on the separator used in this application; any separator known in the art can be used, such as PE (polyethylene) separator, PP (polypropylene) separator, etc.

[0059] In this application, the electrolyte is not particularly limited and any electrolyte known in the art can be used, such as an electrolyte prepared from organic solvents DOL (dioxolane) and DME (dimethyl ether) and LiFSI (lithium bis(fluorosulfonyl)imide) and LiNO3 (lithium nitrate); or an electrolyte prepared from organic solvents DMC (dimethyl carbonate), EMC (ethyl methyl carbonate) and LiPF6, etc.

[0060] The embodiments and comparative examples provided below illustrate the implementation of this application in more detail. Various tests and evaluations were conducted according to the methods described below. Furthermore, unless otherwise specified, "parts" and "%" refer to weight.

[0061] Example 1

[0062] <Preparation of Active Layer>

[0063] a) Preparation of porous hard carbon framework

[0064] Glucose powder is placed in a mold and pressed into glucose sheets under a pressure of 10 tons. Then, it is heated to 800 degrees Celsius for 10 hours under the protection of argon atmosphere to carbonize it, finally obtaining a hard carbon skeleton with a thickness of 50 micrometers, namely a porous carbon skeleton sheet with a porosity of 70%.

[0065] b) Porous carbon framework combined with nano-silicon

[0066] Porous carbon framework sheets were placed in a CVD (chemical vapor deposition) device, and a silane-containing gas was introduced at a flow rate of 100 sccm / min. The CVD device pressure was 30 torr, and deposition was carried out at 500 degrees Celsius for 30 min to obtain porous carbon framework sheets after deposition. The average particle size of silicon nanoparticles in the porous carbon framework sheets after deposition was 20 nm.

[0067] c) Pre-filling lithium

[0068] In a dry argon atmosphere, metallic lithium is placed in a stainless steel crucible and heated to 300 degrees Celsius, melting the solid lithium into a liquid state. A porous carbon framework sheet, after deposition treatment, is then brought into contact with the molten lithium. The lithium metal spontaneously fills the pores of the deposited porous carbon framework sheet, forming the active layer. In this argon atmosphere, the water content is less than 1 ppm, the oxygen content is less than 1 ppm, and the lithium loading in the active layer is 0.5 mg / cm³. 2 .

[0069] <Preparation of Anode Plates>

[0070] In a dry argon atmosphere, the obtained active layer is placed on a nickel current collector with a thickness of 15 μm. The active layer and the nickel current collector are bonded together by hot pressing. The hot pressing temperature is controlled at 300 degrees Celsius and the hot pressing pressure is 100 kg to obtain the anode sheet. The anode sheet is then punched into a size of 40*60 mm for later use.

[0071] <Preparation of Cathode Electrode>

[0072] LiFePO4 (lithium iron phosphate), conductive carbon black, and PVDF (polyvinylidene fluoride) were mixed in a weight ratio of 97.5:1.0:1.5. NMP (N-methylpyrrolidone) was then added as a solvent to prepare a slurry, which was stirred until homogeneous. The slurry had a solid content of 75%. The slurry was then uniformly coated onto a 15 μm thick aluminum foil current collector and dried at 90 degrees Celsius to obtain the cathode electrode. The loading of the cathode active material on the aluminum foil current collector was 1 mg / cm². 2 After coating, the cathode electrode is cut into 38mm*58mm sizes for later use.

[0073] <Preparation of Electrolyte>

[0074] In a dry argon atmosphere, organic solvents DOL and DME were mixed at a volume ratio of DOL:DME = 1:1 to obtain a mixed solvent. LiFSI and LiNO3 were then added to the mixed solvent, dissolved, and mixed thoroughly to obtain the electrolyte. The amount of LiFSI added to the mixed solvent was 1 mol / L, and the amount of LiNO3 added was 1 wt%.

[0075] <Preparation of Lithium-ion Batteries>

[0076] A PE (polyethylene) film with a thickness of 15μm is selected as the separator. A cathode electrode is placed on each side of the anode electrode, and a separator is placed between the cathode electrode and the anode electrode to form a stack. Then, the four corners of the entire stack structure are fixed with tape, placed in an aluminum-plastic film, and after top and side sealing, electrolyte injection, and encapsulation, a lithium metal stacked battery is obtained.

[0077] Example 2

[0078] Except for the deposition time of the porous carbon skeleton sheet in the CVD equipment being 5 minutes, everything else is the same as in Example 1.

[0079] Example 3

[0080] Except for the deposition time of the porous carbon skeleton sheet in the CVD equipment being 120 min, everything else is the same as in Example 1.

[0081] Example 4

[0082] In addition to reducing the amount of pre-added lithium during the preparation of the active layer, the lithium loading in the active layer is controlled to be 0.2 mg / cm³. 2 Except for the above, the rest is the same as in Example 1.

[0083] Example 5

[0084] In addition to increasing the amount of pre-replenished lithium during the preparation of the active layer to control the lithium loading in the active layer to 1 mg / cm³, 2 Except for the above, the rest is the same as in Example 1.

[0085] Example 6

[0086] In addition to increasing the amount of pre-replenished lithium during the preparation of the active layer to control the lithium loading in the active layer to 3 mg / cm³, 2 Except for the above, the rest is the same as in Example 1.

[0087] Example 7

[0088] Except for the use of titanium as the current collector material for the anode electrode, everything else is the same as in Example 1.

[0089] Example 8

[0090] Except for the use of copper as the current collector material for the anode electrode, everything else is the same as in Example 1.

[0091] Example 9

[0092] The lithium-ion battery was prepared using the same method as in Example 1, except that the charging rate was 0.2C when the performance of the prepared lithium-ion battery was tested.

[0093] Example 10

[0094] The lithium-ion battery was prepared using the same method as in Example 1, except that the charging rate was 0.4C when the performance of the prepared lithium-ion battery was tested.

[0095] Example 11

[0096] Except for controlling the average particle size of silicon nanoparticles in the deposited porous carbon framework thin film to 5 nm by lowering the deposition temperature, the rest is the same as in Example 1.

[0097] Example 12

[0098] Except for controlling the average particle size of silicon nanoparticles in the deposited porous carbon framework thin film to 50 nm by increasing the deposition temperature during the preparation of the deposited porous carbon framework thin film, the rest is the same as in Example 1.

[0099] Example 13

[0100] Except for controlling the porosity of the porous hard carbon framework to 40% by lowering the carbonization temperature during preparation, the rest is the same as in Example 1.

[0101] Example 14

[0102] Except for controlling the porosity of the porous hard carbon framework to 90% by increasing the carbonization temperature during preparation, the rest is the same as in Example 1.

[0103] Example 15

[0104] Except for reducing the amount of glucose used to reduce the thickness of the porous carbon framework sheet to 20 micrometers during the preparation of the porous hard carbon framework, the rest is the same as in Example 1.

[0105] Example 16

[0106] Except for increasing the amount of glucose to increase the thickness of the porous carbon framework sheet to 75 micrometers during the preparation of the porous hard carbon framework, the rest is the same as in Example 1.

[0107] Example 17

[0108] Except for increasing the amount of glucose to increase the thickness of the porous carbon framework sheet to 100 micrometers during the preparation of the porous hard carbon framework, the rest is the same as in Example 1.

[0109] Comparative Example 1

[0110] <Preparation of Lithium-Copper Foil Anode Sheets>

[0111] Commercially available lithium-coated copper foil is punched into 40*60mm sizes for use in assembling stacked batteries. The thickness of the lithium-coated copper foil is 30μm.

[0112] Comparative Example 2

[0113] <Preparation of anode plates containing a porous carbon framework, pre-lithiated, and free of silicon nanoparticles>

[0114] a) Preparation of porous carbon framework

[0115] Porous carbon frameworks were prepared using the same method as in Example 1.

[0116] b) Pre-filling lithium

[0117] In a dry argon atmosphere, metallic lithium is placed in a stainless steel crucible and heated to 300 degrees Celsius to melt the solid metallic lithium into a liquid state. The porous carbon framework sheet that has undergone deposition treatment is then brought into contact with the molten lithium phase.

[0118] Then, the anode electrode was prepared using the same anode electrode preparation method as in Example 1.

[0119] Comparative Example 3

[0120] <Preparation of anode plates containing silicon particles but without a carbon framework (non-CVD method)>

[0121] In a dry argon atmosphere, silicon powder particles with an average particle size of 80 nm are mixed with lithium metal at a volume ratio of 1:10. Then, the silicon powder particles and lithium metal are combined by hot pressing. The hot pressing temperature is controlled at 150 degrees Celsius and the pressure is 100 kg to obtain an anode sheet with an average thickness of 30 μm. The anode sheet is then punched into a size of 40*60 mm for use in assembling stacked batteries.

[0122] Comparative Example 4

[0123] <Preparation of anode plates containing a porous carbon framework and silicon particles (CVD method) without pre-lithiation>

[0124] The preparation process of the porous carbon framework is the same as in Example 1.

[0125] The composite process of porous carbon framework and nano-silicon is the same as in Example 1, resulting in a porous carbon framework sheet after deposition treatment. This porous carbon framework sheet is not subjected to pre-lithiation treatment, and the anode electrode preparation method of Example 1 is used directly to obtain the anode electrode.

[0126] Comparative Example 5

[0127] <Preparation of anode plates containing only silicon particles (non-CVD method)>

[0128] Silicon nanoparticles were mixed with polyacrylic acid and conductive carbon in water at a mass ratio of 80:10:10 and stirred until homogeneous to obtain a mixture. This mixture was then coated onto a nickel current collector and dried at 180°C to obtain the anode electrode. The silicon loading in the anode electrode was 1.1 mg / cm³. 2 Then, the anode plates are punched into 40*60mm sizes for use in assembling stacked cells.

[0129] Comparative Example 6

[0130] <Preparation of anode plates containing only a porous carbon framework>

[0131] A porous hard carbon framework was prepared using the method of Example 1, and this porous hard carbon framework was used as an anode electrode.

[0132] Comparative Example 7

[0133] <Preparation of anode plates containing only current collectors>

[0134] The nickel current collector is used directly as the anode electrode.

[0135] Comparative Example 8

[0136] <Preparation of anode plates containing only current collectors and pre-lithiation>

[0137] In a dry argon atmosphere, metallic lithium is placed in a stainless steel crucible and heated to 300 degrees Celsius, causing the solid metallic lithium to melt into a liquid state. A nickel current collector is then brought into contact with the molten lithium, and a small amount of lithium adheres to the surface of the nickel current collector.

[0138] Comparative Example 9

[0139] <Preparation of anode plates containing only current collectors and pre-lithiation>

[0140] The anode sheet was prepared using the same method as in Comparative Example 8, except that the lithium-ion battery made from the anode sheet was charged at a charging rate of 0.4C.

[0141] After obtaining anode plates in Examples 2 to 14 and Comparative Examples 1 to 9, lithium-ion batteries were prepared using the same method as in Example 1.

[0142] Performance Testing

[0143] The lithium-ion batteries prepared in Examples 1 to 8, Examples 11 to 14, and Comparative Examples 1 to 8 were tested using the following methods:

[0144] The lithium-ion batteries prepared in each embodiment were charged and discharged at a rate of 0.1C at 60 degrees Celsius for one cycle, and then charged and discharged at room temperature. The constant current charging stage had a current of 1C and a cutoff voltage of 3.8V, the constant voltage charging stage had a cutoff current of 0.05C, and the constant current discharge stage had a rate of 1C and a cutoff voltage of 2.7V.

[0145] The lithium-ion battery prepared in Example 9 was charged using a charging rate of 0.2C.

[0146] The lithium-ion battery prepared in Example 10 was charged using a charging rate of 0.2C.

[0147] The lithium-ion battery prepared in Comparative Example 9 was charged using a charging rate of 0.4C.

[0148] The volume expansion rates of each embodiment and comparative example were tested and calculated using the following method:

[0149] The cathode and anode plates of each embodiment and comparative example were cut into 10mm × 5mm pieces and polished in an ion polishing machine. The resulting plates were then transferred to a scanning electron microscope (SEM) to observe the cross-sections of the polished plates at a suitable magnification, and the corresponding thicknesses were measured. The thicknesses of the cathode, anode, and separator were then added together to obtain the cell thickness, which does not consider packaging. The cell thicknesses at 0% and 100% charge states were measured using the above method and denoted as t(0%) and t(100%), respectively. The volume expansion rate was calculated using the following formula: Volume expansion rate = (t(100%) - t(0%)) / t(0%).

[0150] The test parameters and corresponding experimental results of Examples 1 to 14 and Comparative Examples 1 to 9 are shown in Table 1 below:

[0151] Table 1 shows the test parameters and corresponding experimental results for each embodiment and comparative example.

[0152]

[0153] As shown in Table 1, although the amount of silicon nanoparticles deposited in Examples 1 to 3 was different, the volume expansion rate was significantly reduced compared with Comparative Examples 1-3, 5, and 7-9; and the number of cycles was significantly increased compared with Comparative Examples 1 to 9.

[0154] Although the amount of pre-replenished lithium added in Examples 4 to 6 was different, the number of cycles was significantly increased compared with Comparative Examples 1 to 9, especially in Example 5, where the volume expansion rate was significantly reduced and the number of cycles was significantly increased.

[0155] Although the current collector materials used in Examples 7 and 8 are different, their volume expansion rate is significantly reduced and the number of cycles is significantly increased compared with Comparative Examples 1 to 9.

[0156] Examples 9 and 10 used different charging rates when testing the performance of the prepared lithium-ion batteries, but compared with Comparative Examples 1 to 9, their volume expansion rate was significantly reduced and the number of cycles was significantly increased.

[0157] Although the average particle size of the silicon nanoparticles in Examples 11 and 12 is different, their volume expansion rate is significantly reduced and their cycle number is significantly increased compared with Comparative Examples 1 to 9.

[0158] Although the porosity of the porous hard carbon framework differs in Examples 13 and 14, its volume expansion rate is significantly reduced and the number of cycles is significantly increased compared to Comparative Examples 1 to 9.

[0159] In Examples 15 to 17, when the thickness of the porous carbon sheet is relatively low relative to the cathode active material loading (as in Example 15), the internal pores of the electrode are insufficient to accommodate all the pre-filled and deposited lithium. This results in some lithium depositing on the electrode surface, leading to increased volume change and deteriorated cycling performance. When the thickness is increased to 75 micrometers and 100 micrometers, the increased thickness slightly improves volume expansion at the expense of energy density; however, the increased specific surface area reduces cycling performance. Therefore, the optimal thickness should be determined by comprehensively considering energy density, volume expansion, and cycling count, in conjunction with the cathode loading.

[0160] In Comparative Example 1, the battery prepared using only lithium-coated copper foil anode plates showed a significantly higher volume expansion rate and a significantly lower cycle life compared to the batteries prepared in Examples 1 to 17.

[0161] In Comparative Example 2, when the anode electrode does not contain silicon nanoparticles, the volume expansion rate is significantly higher and the number of cycles is significantly lower compared with the batteries prepared in Examples 1 to 17.

[0162] In Comparative Example 3, when the anode electrode contained silicon particles but no carbon skeleton, the volume expansion rate was significantly increased and the number of cycles was significantly decreased compared with the batteries prepared in Examples 1 to 17.

[0163] In Comparative Example 4, when the anode electrode contained silicon particles, but not silicon nanoparticles prepared by the SVD method, and did not contain pre-lithiation, the volume expansion rate did not change much compared with the batteries prepared in Examples 1 to 17, but the number of cycles decreased significantly.

[0164] In Comparative Example 5, when the anode electrode contained only silicon particles (non-CVD method) and no carbon skeleton or pre-lithiation, the volume expansion rate was significantly higher than that of the batteries prepared in Examples 1 to 17, but the number of cycles was significantly lower.

[0165] In Comparative Example 6, when the anode electrode contained only a porous carbon skeleton and no pre-lithiation was included, the volume expansion rate did not change much compared with the batteries prepared in Examples 1 to 17, and the number of cycles decreased significantly.

[0166] In Comparative Example 7, when the anode electrode contained only current collectors and no carbon skeleton or pre-lithiation, the volume expansion rate was significantly higher and the number of cycles was significantly lower compared to the batteries prepared in Examples 1 to 17.

[0167] In Comparative Example 8, when the anode electrode contained only current collector and pre-replenished lithium, the volume expansion rate was significantly increased and the number of cycles was significantly decreased compared with the batteries prepared in Examples 1 to 17.

[0168] In Comparative Example 9, when the anode electrode contained only current collector and pre-replenished lithium, and was charged at a charging rate of 0.4C, the volume expansion rate was significantly increased and the number of cycles was significantly decreased compared to the batteries prepared in Examples 1 to 17.

[0169] The above description is only a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the scope of protection of this application.

Claims

1. An anode electrode comprising a current collector and an active layer, the active layer comprising a porous carbon framework and silicon nanoparticles and lithium metal located within the porous carbon framework; in, The porous carbon framework is a membrane-like structure with pores, and the porosity of the porous carbon framework is 40% to 90%. The lithium metal content in the active layer is 0.5 to 1 mg / cm³. 2 The sum of the volumes of the porous carbon framework and the silicon nanoparticles accounts for 10% to 60% of the total volume of the active layer; the thickness of the active layer is 50 to 100 μm. The total volume ratio of the porous carbon framework to the silicon nanoparticles is 5:1 to 100:

1.

2. The anode electrode according to claim 1, wherein, The strength of the porous carbon skeleton is not less than 200 GPa.

3. The anode electrode according to claim 1, wherein, The material of the current collector includes at least one of copper, nickel, titanium, molybdenum, iron, zinc, stainless steel, carbon, or graphene.

4. A lithium-ion battery, comprising: Cathode electrode; Anode plate; A separating membrane is located between the cathode electrode and the anode electrode; as well as Electrolyte; Wherein, the anode electrode is the anode electrode as described in any one of claims 1 to 3.

5. An electronic device comprising the lithium-ion battery of claim 4.

Citation Information

Patent Citations

  • Silicon-carbon nanotube microspheres and metal lithium compound thereof, and preparation method and application

    CN106684342A

  • Silicon-coated perpendicular graphene / metallic lithium composite material, method for preparing same and application of silicon-coated perpendicular graphene / metallic lithium composite material

    CN106898753A

  • Composite lithium negative electrode, preparation method thereof and lithium ion battery

    CN109473629A

  • Composite lithium metal negative electrode, preparation method and lithium ion battery

    CN109713224A

  • Manufacturing method of flexible three-dimensional metal lithium negative electrode material

    CN110556535A